2010
DOI: 10.1371/journal.pone.0011307
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal PPARδ Activation and Myostatin Inhibition Exert Distinct yet Complimentary Effects on the Metabolic Profile of Obese Insulin-Resistant Mice

Abstract: BackgroundInterventions for T2DM have in part aimed to mimic exercise. Here, we have compared the independent and combined effects of a PPARδ agonist and endurance training mimetic (GW501516) and a myostatin antibody and resistance training mimetic (PF-879) on metabolic and performance outcomes in obese insulin resistant mice.Methodology/Principal FindingsMale ob/ob mice were treated for 6 weeks with vehicle, GW501516, PF-879, or GW501516 in combination with PF-879. The effects of the interventions on body com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 38 publications
5
61
1
Order By: Relevance
“…Specifically, activation of PPAR␤/␦ results in increased utrophin A transcript levels in mdx mice (a model of Duchene muscular dystrophy), which is a protein that can functionally compensate for the loss of dystrophin in mdx mice and as such helps to maintain the sarcolemmal integrity of degenerating muscle fibers. A very recent study reports that postnatal activation of PPAR␤/␦ results in a similar effect on muscle metabolism to that observed following inhibition of myostatin (24), a TGF-␤ superfamily member and potent negative regulator of myogenesis (25,26). Postnatal activation of PPAR␤/␦ by GW501516 and neutralization of myostatin activity via PF-879 antibody in ob/ob mice results in reduced fat mass, improved glucose tolerance, and reduced muscle triglyceride and free fatty acid levels (24); this study clearly demonstrates that there is some degree of similarity between PPAR␤/␦ activation and myostatin inhibition, at least during postnatal growth.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Specifically, activation of PPAR␤/␦ results in increased utrophin A transcript levels in mdx mice (a model of Duchene muscular dystrophy), which is a protein that can functionally compensate for the loss of dystrophin in mdx mice and as such helps to maintain the sarcolemmal integrity of degenerating muscle fibers. A very recent study reports that postnatal activation of PPAR␤/␦ results in a similar effect on muscle metabolism to that observed following inhibition of myostatin (24), a TGF-␤ superfamily member and potent negative regulator of myogenesis (25,26). Postnatal activation of PPAR␤/␦ by GW501516 and neutralization of myostatin activity via PF-879 antibody in ob/ob mice results in reduced fat mass, improved glucose tolerance, and reduced muscle triglyceride and free fatty acid levels (24); this study clearly demonstrates that there is some degree of similarity between PPAR␤/␦ activation and myostatin inhibition, at least during postnatal growth.…”
mentioning
confidence: 69%
“…A very recent study reports that postnatal activation of PPAR␤/␦ results in a similar effect on muscle metabolism to that observed following inhibition of myostatin (24), a TGF-␤ superfamily member and potent negative regulator of myogenesis (25,26). Postnatal activation of PPAR␤/␦ by GW501516 and neutralization of myostatin activity via PF-879 antibody in ob/ob mice results in reduced fat mass, improved glucose tolerance, and reduced muscle triglyceride and free fatty acid levels (24); this study clearly demonstrates that there is some degree of similarity between PPAR␤/␦ activation and myostatin inhibition, at least during postnatal growth. Given the benefits associated with PPAR␤/␦ activation and skeletal muscle growth, we attempted to delineate the mechanism(s) through which PPAR␤/␦ regulates muscle growth.…”
mentioning
confidence: 69%
“…Indeed, myostatin knockout mice display increased energy expenditure (29) and protection against lipid-induced insulin resistance, glucose intolerance, and HFD-induced obesity (16,(30)(31)(32). In contrast with these studies, LeBrasseur et al (27) did not observe an improvement in glucose tolerance and insulin sensitivity in aged …”
Section: Discussionmentioning
confidence: 92%
“…In extremely obese human participants it was further discovered that there were elevated levels of MSTN protein in both muscle and plasma samples [17]. In addition, injection of MSTNspecific antibodies along with exercise results in significantly increased insulin sensitivity [18]. Recently, Guo et al showed that inhibition of MSTN signalling, specifically in adipose tissue, had no effect on glucose and insulin tolerance [12].…”
mentioning
confidence: 99%